SOLAR ENERGY CONVERSION - COMPUTER-AIDED EXPERIMENT - GERHÁTOVÁ, Žaneta (Trends in education, 2013)
In this paper we present the results of testing the electrochemical organic solar cell, of our construction. The cell is a part of the computer aided experiment "Solar energy conversion". We present the current-voltage characteristics of the solar cell and fill factor FF at 100 % light intensity. In the construction of electrochemical organic solar cell as a source of dye anthocyanins we used raspberry. We used tools that are part of the "Solar Man-Article N° 3000".
Keywords: anthocyanin; experiment; organic electrochemical cell; solar energy